P–486 Psychological determinants of the decision to attend couples infertility counselling. (6th August 2021) - Salvatori, P; Andrei, F; Cipriani, L; Damiano, G; Dirodi, M; Labriola, F S; Rossi, N; Porcu, E
Abstract: Study question: May specific psychological variables related to the experience of infertility have a predicting effect over the decision of accepting counselling? Summary answer: Specific infertility related sources of sufferance including low levels of infertility self-efficacy and poor quality of life significantly predict the request for professional help. What is known already: Available data on the access to infertility counselling services suggest that only 10–34% of patients who are offered such opportunity actually pursue it. Qualitative studies pointed out that this might be due to a lack of information about available support and to negative attitudes toward counselling. It seems also that women and men who accept counselling have worse levels of psychological distress. However, there is a lack of quantitative studies on the topic and among those available none used measures that are specific to the experience of infertility itself Study design, size, duration: The data presented herein are part of a larger data collection promoted by the Italian Ministry of Health on the psychological impact of assisted reproduction. The present study is a cross-sectional research and involves a sample of 184 patients, composed by 92 women waiting for infertility treatment and their partners, enrolled between October 2019 and October 2020 at the Infertility and IVF Unit of the S. Orsola University Hospital in Bologna, Italy. Participants/materials, setting, methods: Participants were voluntarily enrolled in the study at their first medical consult. They were informed about the possibility to attend free couples infertility counselling sessions and asked to fill in the following questionnaires: Infertility Self-Efficacy Scale (ISE); Fertility Quality of Life (FERTIQoL); Dyadic Adjustment Scale (DAS). To attend infertility counselling a shared agreement between partners was requested. Couples who agreed to the study but not to counselling sessions were provided only with questionnaires. Main results and the role of chance: The 34.8% (n = 32 couples) of the sample accepted to receive counselling sessions. The two groups (counselling vs no-counselling) were comparable in all socio-demographic variables, aside for education, with higher education levels in the counselling group. Overall, the counselling group reported greater psychological sufferance than the no-counselling group, with lower scores at the ISE, FERTIQoL, and DAS questionnaires. Regarding which factors predicted the decision to attend counselling sessions, logistic regression analysis showed that: for the female partner's dimensions low scores at the ISE and at the Emotional subscale of the FertiQoL were predictive of accepting counselling (when scores increased the odds of being in the counselling group would decrease by 46% and 8% respectively); for the male's partner dimensions, predictive factors were low scores on the Social subscale and high scores on the Relational subscale of the FertiQoL (when scores increased the odds of being in the counselling group would decrease by 8% and increase by 10% respectively). In conclusion, impairments in self-efficacy, emotional well-being and social life may drive a greater need for help, but a close relationship with the partner may be also necessary to predispose men to accept couples infertility counselling. Limitations, reasons for caution: Data were collected from a well enough homogeneous sample which may have helped in better enhancing the specificity of infertile couples' needs. However, the small sample size and the fact that data were collected from a sole Italian clinic may impact the representativity of our results. Wider implications of the findings: Findings provide important information for clinical interventions with infertile couples. Patients accepting counselling might be having a worse adjustment to the experience of infertility. Besides, women and men may be affected in different ways. Men's closeness to the partner might be a favourable factor and should be further studied. Trial registration number: The study was approved by the Ethical Committee of the S. Orsola Hospital, University of Bologna (CE: 273/2018/Sper/AOUBO) and funded by the Italian Ministry of Health (J33C17000560001)